God as a connection between religion and philosophy in Friedrich D.E. Schleiermacher (Research, Society and Development, 2020)
The purpose of this article is to introduce, in an introductory way, the philosophical thought of Friedrich D.E. Schleiermacher, as well as demonstrating the connection of the German philosopher's philosophical enterprise with his theory of religion. Schleiermacher's Dialectic work, a posthumous work and not properly prepared for publication, addresses the transcendental dimension of thought, that is, it shows the principles on which the unity, validity and integrity of human knowledge are based, principles that seek to guide the in the development of thinking until you know it. However, this agreement between being and thinking is not found in pure thought, but in what the author calls the transcendent foundation of knowledge. The transcendent foundation is the foundation of knowledge and is configured as the link between philosophy and religion in the thought of the German philosopher, since Schleiermacher identifies it with the idea of God or deity. This transcendent foundation is presented to the experience not in a purely rational way, but as a feeling. The feeling is configured as the filling of the gap found between God and man in the activities of thought and knowledge. Finally, we will point out how Schleiermacher seeks to dissolve the polarity between being and thinking through the conception of God.